The Influence of Price, Promotion, and Service Quality on Purchase Decisions (A Study on Consumers of Viar Mitraindo Dealer in Ciledug, Tangerang City) - Supriatin, Ai Iis; Vildayanti, Rina Ayu (Jurnal Multidisiplin Sahombu, 2025)
This study aims to examine the influence of price, promotion, and service quality on consumer purchase decisions at Viar Mitraindo Dealer Ciledug. The research adopts a quantitative approach with data collected through structured questionnaires distributed to respondents who have made purchasing decisions at the dealer. Data analysis was conducted using statistical techniques to evaluate both partial and simultaneous effects of the independent variables on the dependent variable. The findings reveal that price and service quality significantly influence purchase decisions, while promotion does not demonstrate a strong individual effect. However, when considered together, all three variables collectively contribute to shaping consumer choices. These results highlight the importance of maintaining competitive pricing and ensuring service excellence as key strategies for enhancing customer decision making. The study provides managerial implications for strengthening marketing strategies in the highly competitive automotive sector.